It’s the Little Things: The Role of Microscopic Life Stages in Maintaining Kelp Populations - Matthew S. Edwards (Frontiers in Marine Science, 2022)
Kelp forests are experiencing broad scale declines in abundance and shifts in latitudinal ranges in many areas of the world due to numerous environmental stressors, especially those associated with climate change. While the majority of studies on kelp ecology have focused exclusively on the macroscopic sporophyte life stage, a growing number of studies is showing quite convincingly that the microscopic zoospore and gametophyte life stages can be important to establishing spatial patterns in these marine forests, and in facilitating their recovery following deforestation. Unfortunately, their microscopic sizes have made them difficult to study in the field, leading to a ‘black box’ surrounding what we know about their ecologies. However, advances in experimental methodologies and a growing number of laboratories studying kelp microscopic life stages are revealing how they are affected by variability in environmental conditions, and are providing a clearer picture of how kelp forests might respond to a changing ocean climate. These studies have largely revealed that kelps can disperse over a wide range of distances, enhanced by the synchronous release and vertical transport of zoospores into shallower water, and by floating rafts of reproductive thalli. Settlement on the benthos is facilitated by both positive and negative chemotaxis, and by active selection of microhabitats that favor their growth and survival. Following settlement and subsequent germination, the haploid gametophytes can delay their development and form a bank of microscopic forms that persist during periods that are unfavorable for the large sporophyte populations, or they can develop and undergo sexual reproduction during which they respond to variability in environmental conditions. In particular, they are strongly affected by increases in irradiance (PAR, UVA + UVB) and temperature, decreases in nutrients and salinity, and by sedimentation and grazing. However, the manner in which they respond to these stressors varies among species and with their geographic distributions, which is integral to establishing biogeographic patterns in the large sporophyte populations. Given these factors are expected to change as the ocean climate changes, these species-specific responses have significant implications for future patterns of distribution and abundance of these iconic marine forests.